Occurrence and distribution of viral diseases on vanilla (Vanilla planifolia Andrews) in India - Suseela Bhai, A I Bhat, M N Venugopal, R P Pant, R (Journal of Spices and Aromatic Crops, 2004)
Sixty-five vanilla (Vanilla planifolia) plantations in 28 locations of Karnataka and Kerala were surveyed for the occurrence and distribution of viral diseases. Two viral diseases namely, mosaic and stem necrosis with an average incidence ranging from 0% to 5% and 0% to 10%, respectively, in various locations were noticed. The distribution of the diseases was random and not restricted to any particular region or locality. Electron microscopy of leaf dip preparations of the diseased plants showed three kinds of flexuous particles resembling Potexvirus, Potyvirus and Closterovirus, and an isometric particle.